ANALYSIS OF MEDAN-SIBOLGA LAND TRANSPORT MODE CHOICE USING STATED PREFERENCE METHOD: ANALISA PEMILIHAN MODA TRANSPORTASI DARAT MEDAN-SIBOLGA DENGAN METODE STATED PREFERENCE - Bakar, Abu (UPMI Proceeding Series, 2023)
This research aims to analyze the choice of land transportation modes in Medan-Sibolga using the method of stating preferences. This chapter will explain the stages in research so that research is more focused, efficient, effective and does not deviate from the boundaries of the problem so that the objectives of the research can be achieved. The population here is the number of daily bus passengers and trips to Medan-Sibolga. To determine the number of samples from the population in this case, the number of samples for each mode of transportation is based on the number of passengers per day in each mode with a value of e = ±10%. So the total number of samples required is 100 passengers coming from the bus station. , and traveling in Medan. The expected results from research are the objectives of a research. The aim of this research is to determine the characteristics of travelers using public transportation, buses and travel. Primary data consists of the characteristics of the respondent's traveler including the origin and destination of the user, age of the user, occupation and fare paid by the user as well as the reasons for choosing the vehicle mode. From the analysis, it is stated that preferences between travel modes and buses on the Medan-Sibolga route are obtained based on the ticket price attribute when the travel price is IDR 90,000, the potential for travel passengers is 40%, namely 30 people per day, then when the ticket price is IDR. 110,000 potential travel passengers is 30%, namely 30 people per day and when the ticket price is IDR 120,000, the potential for travel passengers is 45%, namely 40 people per day. Based on the travel time attribute, when the travel time is 9 hours 30 minutes, the potential for travel passengers is 40%, namely 34 people per day, and when the travel time is 9 hours 45 minutes, the potential for passengers is 60%, namely 56 people per day.